Publishing Skopje Air Quality Data as Linked Data - Jovanovik, Milos; Mishev, Kostadin; Kjosevski, Angjel; Kalemdzhievski, Nikola; Koteli, Nikola; Mitreski, Kosta; Trajanov, Dimitar (Faculty of Computer Science and Engineering, Skopje, 2015)
— Publishing raw data as Linked Open Data gives an opportunity of data reusability and data understandability for the computer machines. Today, the air pollution problem is one of the biggest in the whole world. Republic of Macedonia, especially its capital Skopje, has big problems with the PM2.5 and PM10 particles in the air approved by several measurement stations positioned on several locations in Skopje. In this paper, we demonstrate the process of centralizing of all the data collected from different measurement stations in one database. Also, we enable interpolation of collected data providing information about the current air quality state in the area between the measurement stations using previously implemented eco models. Interpolated data is saved in the same database providing interfaces that transform saved data into four-star and five-star data, by reusing the existing ontologies from the domain and linking them to the physical places where the measurements were taken and the interpolations were calculated. As a use case scenario, we provide and heat map about the values from various pollutants in the areas in Skopje providing information about the regions that have problems with air pollution.
Keywords: air quality, indicator, measurements, measurement interpolation, ecoinformatics, open data, linked data